A homologue of the vertebrate SET domain and zinc finger protein Blimp-1 regulates terminal differentiation of the tracheal system in the Drosophila embryo. - Ng, T.; Yu, F.; Roy, S. (Development genes and evolution, 2006)
The B-lymphocyte-inducing maturation protein (Blimp-1) gene encodes a zinc finger and SET/PR domain-containing transcriptional factor. A number of functional studies in a variety of vertebrate species have demonstrated that Blimp-1 is a master regulator of cell fate determination and cell differentiation in a wide diversity of developmental contexts. Despite all of this significance, the role, if any, of a homologue of Blimp-1 in directing morphogenetic events during embryonic development of invertebrates has so far remained completely unexplored. In this report, we describe the identification of a Drosophila homologue of Blimp-1 and show that the gene is expressed in diverse cell types during the course of embryogenesis. Further, using genetic analysis, we demonstrate that its wild-type activity is critically required for the maturation of the tracheal system into properly differentiated tubes.